3D-QSAR studies on indole and 7-azoindole derivatives as ROCK-2 inhibitors: An integrative computational approach. (December 2017) - Nagarajan, Santhosh Kumar; Babu, Sathya; Sohn, Honglae; Devaraju, Panneer; Madhavan, Thirumurthy
Graphical abstract: Highlights: A 3D QSAR study of indoles and 7-azoindoles derivatives as ROCK2 inhibitors is reported. Three different molecular alignment techniques were used – systematic search, simulated annealing and pharmacophore. CoMFA and CoMSIA models with good statistical values were obtained. The results correlate the structural features of the molecules with the inhibitory activities against ROCK2. Abstract: Rho Kinases (ROCK) has been found to regulate a wide range of fundamental cell functions such as contraction, motility, proliferation, and apoptosis. Recent experiments have defined new functions of ROCKs in cells, including centrosome positioning and cell-size regulation, which might contribute to various physiological and pathological states. In this study, we have performed pharmacophore modeling and 3D QSAR studies on a series of 36 indoles and 7-azoindoles derivatives as ROCK2 inhibitors to elucidate the structural variations with their inhibitory activities. Ligand based CoMFA and CoMSIA models were generated based on three different alignment methods such as systematic search, simulated annealing and pharmacophore. A total of 15 CoMFA models and 27 CoMSIA were generated using different alignments. One model from each alignment is selected based on the statistical values. Contour maps of the selected models were compared, analysed and reported. The 3D QSAR study revealed that electro positive group linked to the methoxy-benzene ring position of the structure will enhance the biological activity and bulkier substitutions are preferred in the methyl dihydroindole region. Also, it is found that the hydrogen bond donor substituted at the R1 position enhances the inhibitory activity. In future, this study would give proper guidelines to further enhance the activity of novel inhibitors for ROCK2.